The relationship of intelligence and self-concept to mathematics achievement among the grade five pupils of the University of San Carlos Girls' High School for the school year 1974-1975 - Almendras, Enrica S.
Intelligence quotients and self-concepts of the "high" achievers, "average" achievers and "low" achievers in mathematics among the grade five pupils of the University of San Carlos Girls' High School in Cebu City of school year 1974-1975 were determined in this study.